Incorporation of Terbium into a Microalga Leads to Magnetotactic Swimmers. Issue 12 (24th September 2018) - Santomauro, Giulia; Singh, Ajay Vikram; Park, Byung‐Wook; Mohammadrahimi, Mohammadreza; Erkoc, Pelin; Goering, Eberhard; Schütz, Gisela; Sitti, Metin; Bill, Joachim
Abstract: Swimming microorganisms have been shown to be useful for the propulsion of microrobotic devices due to their self‐powered motion. Up to now, mainly bacteria, e.g., magnetotactic bacteria (MTB), are investigated as biohybrid microrobots. But biocompatibility studies of MTB regarding medical utilizations are still lacking. Moreover, MTB require special culture conditions for their stability, which also might limit their usage for biomedical applications. Herein, a cytocompatible, highly motile microswimmer is presented from a microalga, Chlamydomonas reinhardtii, which has the capacity to carry large loads. C. reinhardtii cells are magnetized by incorporating terbium. The following analyses reveal an induced magnetic moment of a magnetized C. reinhardtii cell of 1.6 × 10 −11 emu, comparable to its counterparts used as magnetotactic microrobots. The magnetized algae are able to align to the field lines of an applied uniform magnetic field, guiding them to swim in a directional motion. In addition, C. reinhardtii cells and human cells show mutual biocompatibility, indicating that the algae cells are noncytotoxic. Furthermore, the magnetized microalgae reported here are easy to track in the human body by luminescence imaging tools due to their innate autofluorescence performance and photoluminescence of the incorporated Tb 3+ . Thus, terbium‐incorporated microalgae are promising candidates for magnetically steerable biohybrid microrobots. Abstract : Magnetotactic microalgae are facilely generated by accumulation of magnetic terbium ions inside the living cells. The fast swimming algae can be controlled magnetically, they align passively to magnetic field lines and swim actively towards the magnets. They have fluorescence properties due to the lanthanide terbium and show mutual biocompatibility with mammal cells. The reported magnetotactic microalgae display promising candidates for microrobotic devices.